Design of Web Based Academic Information System in Madrasah Ibtidaiyah Nurul Falah Depok - Ibnu Rusdi; Bekti Kurniasih (Jurnal Riset Informatika, 2020)
Madrasah Ibtidaiyah Nurul Falah Depok still does not have a system that can be widely accessed because it is still not computerized, as in general it has not made full use of technology. Giving daily test scores, midterm exams (UTS), semseter final exams (UAS) are still being done by teachers or teachers. Students at these schools cannot directly see the grades given by the teacher or teacher because the final grades are given when all have been recapitulated and are in the form of report cards at the end of the semester. The research method used is quantitative and applied methods so that using these two methods can make a good contribution to the research and development of information systems that are designed and will be used in MI Nurul Falah. The System Development Life Cycle used in this software development is the Waterfall model with several stages starting from analysis, design, coding and testing. To design the proposed database in the form of ERD and LRS, for system design using UML. The research objective is expected that the software built can be maximized in terms of data security and its use in academic and non-academic fields. The results of research related to academic information regarding access to grades and other notices are very important in order to motivate students to prepare themselves better and study actively in facing the learning process in one semester so that access to this information makes it easier for parents to be able to monitor and control their children in the field of academic achievement.